Detection the role of physiological factors to produce carotenoid pigment in Staphylococcus aureus - Ghada A. Mohammad; Suhair Taha Daod (Tikrit Journal of Pure Science)
Three Staphylococcus aureus isolates were used in the present study for extraction and quantitation of carotenoid pigment production. Different culture conditions were used to determine optimum pigmentation such as type of culture media, different pH values, temperature, and finally daily bacterial sub-culturing for more than 2 weeks. Nutrient agar was found to be the best medium with the highest production (1.09). Optimum pH value was 6.5 and gave (1.8) carotenoid. Also results showed that pigment was produced at 37o C more than at 42oC. Daily repeated sub culturing had a negative impact on pigment production. Colonies gradualy lost pigmentation and became white in color. Also, sub-culturing was shown to affect the volume of the colonies as they became smaller on solid media.